2021
DOI: 10.1093/ofid/ofab119
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes and Risk Factors of Septic Shock in Patients With Infective Endocarditis: A Prospective Cohort Study

Abstract: Background Little is known about the characteristics and impact of septic shock (SS) on the outcomes of infective endocarditis (IE). We aimed to investigate the characteristics and outcomes of patients with IE presenting with SS and to compare them to those of IE patients with sepsis (Se) and those with neither Se nor SS (no-Se-SS). Methods Prospective cohort study of 4,864 IE patients from 35 Spanish centers (2008 to 2018). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 20 publications
0
14
0
Order By: Relevance
“…2,3,7,10,[108][109][110] Of note, sepsis and septic shock are associated with a fourfold increase in the probability of death. [111][112][113] Studies on psychological outcomes in endocarditis survivors have demonstrated-in addition to the possibility of sequelae in the form of heart failure due to valve dysfunction, neurological alterations due to embolic phenomena, or residual osteoarticular lesions after spondylitis or septic arthritis-reductions in the quality of life and the occurrence of posttraumatic stress disorder. 114…”
Section: Prognosismentioning
confidence: 99%
“…2,3,7,10,[108][109][110] Of note, sepsis and septic shock are associated with a fourfold increase in the probability of death. [111][112][113] Studies on psychological outcomes in endocarditis survivors have demonstrated-in addition to the possibility of sequelae in the form of heart failure due to valve dysfunction, neurological alterations due to embolic phenomena, or residual osteoarticular lesions after spondylitis or septic arthritis-reductions in the quality of life and the occurrence of posttraumatic stress disorder. 114…”
Section: Prognosismentioning
confidence: 99%
“…In a US population based-study, complications associated with increased mortality rates were reported in nearly 40% of patients [3 ▪ ]. Likewise, in a large European study, the outcome of IE patients with septic shock was poor, with a 1-year mortality rate approximating two-thirds [4 ▪ ]. Despite these data, few well conducted studies or reviews are dedicated to critically ill IE patients.…”
Section: Introductionmentioning
confidence: 99%
“…These seminal studies are consistent with clinical findings, as S. aureus is the most common pathogen in patients with IE, followed by Streptococcus and Enterococcus species [2 ▪ ]. Furthermore, in a cohort of ICU patients with IE-related septic shock, S. aureus was the main agent responsible for the infection [4 ▪ ]. A significant increase in Enterococcus -associated IE has been reported consistently over the past decade, likely related to the increased frequency of transcatheter procedures in the elderly, as the femoral microbiota of the elderly has been documented as displaying a higher incidence of enterococcal colonization [1,2 ▪ ,14].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations